#OMFSurgery: analyzing the use of social media applications in oral and maxillofacial surgery resident training - Seifert, Lukas Benedikt; Becker, Philipp; Pabst, Andreas; Sander, Anna K.; Schneider, Josephine; Schorn, Lara; Zeller, Alexander; Hoffmann, Jürgen; Thiem, Daniel G. E. (BMC oral health, 2023)
Background: Despite its increasing popularity, to our knowledge the use of social media applications (SM) for residents’ training in Oral and Maxillofacial Surgery (OMFS) has not been investigated yet. The aim of this study was to evaluate the use of SM applications by OMFS residents for post-graduate training in Germany. Methods: For explorative assessment, an online questionnaire containing 27 questions about the current use of SM for resident training was sent to OMFS residents in Germany. Results: Sixty-four colleagues participated to the study. Thirty-four participants (54%) responded to regularly use those platforms mainly for OMFS-related content. YouTube (65%, n = 37), Instagram (48%, n = 27), ResearchGate (25%, n = 14) and WhatsApp (16%, n = 9) were the most popular platforms. (Surgical) videos (97%, n = 59), pictures and graphics (82%, n = 50) were the mainly accessed contents. Forty-four participants (69%) stated that SM substantially contributed to their OMFS training. Dentoalveolar surgery and implantology (66%, n = 35) and aesthetic facial surgery (55%, n = 29) content contributed most to OMFS resident training. Fifty-one participants (80%) recommended an official SM account of the DGMKG. Conclusions: SM is frequently used by OMFS residents for the consumption of training-related content. There is an imbalance toward dentoalveolar and facial aesthetic surgery regarding the presented content. Academic institutions and societies should complement their educational activities to not miss this emerging educational innovation. Official SM content by academic institutions and societies could contribute to the existing educational activities.
Gesehen am 22.05.2023